2015
DOI: 10.1038/srep15270
|View full text |Cite
|
Sign up to set email alerts
|

EGCG antagonizes Bortezomib cytotoxicity in prostate cancer cells by an autophagic mechanism

Abstract: The proteasome inhibitors Bortezomib (BZM) and MG132 trigger cancer cell death via induction of endoplasmic reticulum (ER) stress and unfolded protein response. Epigallocatechin gallate (EGCG), the most bioactive green tea polyphenol, is known to display strong anticancer properties as it inhibits proteasome activity and induces ER stress. We investigated whether combined delivery of a proteasome inhibitor with EGCG enhances prostate cancer cell death through increased induction of ER stress. Paradoxically, EG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 52 publications
1
46
0
3
Order By: Relevance
“…Similar effects have been described for two synthetic enantiomeric analogs of natural GTCs in PCa cells [133]. The observed accumulation of short-lived proteins, normally addressed to proteosomal degradation such as p21, p27, Bax and ikΒα, in PCa cells after EGCG or GTCs treatment indirectly confirms, that GTCs exert inhibitory effect on the proteasome activity [98,134].…”
Section: Proteasome Inhibitionsupporting
confidence: 73%
“…Similar effects have been described for two synthetic enantiomeric analogs of natural GTCs in PCa cells [133]. The observed accumulation of short-lived proteins, normally addressed to proteosomal degradation such as p21, p27, Bax and ikΒα, in PCa cells after EGCG or GTCs treatment indirectly confirms, that GTCs exert inhibitory effect on the proteasome activity [98,134].…”
Section: Proteasome Inhibitionsupporting
confidence: 73%
“…We next examined whether p21 induction was mediated by the inhibition of autophagy-induced protein degradation after treatment with CQ or AQ [2426]. As previously reported [27,28], CQ treatment increased the level of the autophagosome membrane-bound form of LC3B. AQ also strongly increased the level of LC3B degradation via autophagy but had no effect on ATG5 expression (Fig.…”
Section: Resultsmentioning
confidence: 70%
“…Recently, it has been suggested that autophagy plays a critical role in the resistance of PCa cells to hormonal therapy or chemotherapy and that inhibition of autophagy synergizes with docetaxel or androgen deprivation [15,16]. Combined treatment of several different cancer cell lines with autophagy suppressive agents and bortezomib increases cell death and improves clinical response in patients with relapsed multiple myeloma [1719]. Further, proteasome inhibitor-resistant PCa cells are thought to utilize autophagy to resist this class of drugs [20].…”
Section: Introductionmentioning
confidence: 99%